Mediating Role of Fashion Consciousness on Cosmopolitanism and Status Consumption of Young Fashion Consumers in Sri Lanka - ., Jayarathne; ., . (International Journal of Engineering and Technology, 2018)
The aim of this paper is to examine the mediating role of fashion consciousness on cosmopolitanism and status consumption of young fashion consumers in Sri Lanka. A survey method is used. The result uncovers that the fashion consciousness fully mediates the relationship between cosmopolitanism and status consumption of young fashion consumers in Sri Lanka. Finally, the paper provides important implications and suggestions for practitioners as well as for academics in the field of consumer behavior.Â Â